Australian Health Services Management Courses: A discussion on syllabus - Yen, Margaret; Anderson, Judith (Asia Pacific journal of health management, 2023)
OBJECTIVE The aim of this research was to understand core knowledge areas offered by master's courses in health services management in Australian universities. DESIGN A Google search identified relevant Masters' degrees in health services management. Course syllabus was then extracted from each university's website. Common core subjects were then collated and compared. SETTING Data for this study was collected from Australian university websites. MAIN OUTCOME MEASURES Findings were compared with those presented in a similar study conducted in 2013. Interpretation was also informed by an appraisal of key issues that characterise the current context of health care in Australia. RESULTS Masters' degrees in health services management were offered by 18 universities. Common core subjects included management, evaluation, evidence, health system, governance, law and human resource management. A comparison with an earlier study conducted by Ritchie and Yen [1] found an increase in the following subjects: health system, quality management, health economics, policy and research, and a decrease in health information, epidemiology and resourcing. New knowledge areas included leadership, planning and project management, change management, and strategy. CONCLUSIONS This paper presents a discussion on knowledge areas that comprise syllabus in Masters level health services management education nationally. Key findings revealed differences between courses and the responsiveness of core syllabus to the current health care environment. The emergence of leadership, planning and project management was unsurprising while an absence of subjects that gave explicit reference to First Nations peoples was a notable finding.